Seasoning hydrous pyrolysis reactor vessels. (August 2017) - Snowdon, Lloyd R.; Jiang, Chunqing; Nightingale, Michael; Snowdon, Ryan W.
Graphical abstract: Fresh 316 stainless steel lathe turnings were blackened by heating with distilled water at 250 °C for ∼20 h under an Ar atmosphere. Highlights: Fresh stainless steel surfaces heated with H2 O at 250 °C blackened. The blackening was due to oxidation occurring in 20 h or less. Hydrogen gas was present in the headspace after heating at 250 °C. Temperature overshoot of the Parr Instruments reactor was ≤ 1 °C. Abstract: Fresh stainless steel (316) surfaces were blackened by heating at 250 °C for 2–20 h in the presence of water and argon. Headspace gas after heating contained up to 1 mol% molecular hydrogen. These results indicate that the water oxidized the metal surfaces causing the blackening and released molecular hydrogen. Oxidation must be considered as an alternative or complementary process to carburization during the seasoning of 316 stainless steel reactor vessels during hydrous pyrolysis.